Plasma Pyridoxal 5´-Phosphate Level in Children with Intractable and Controlled Epilepsy - PIRZADEH, Zahra; GHOFRANI, Mohammad; MOLLAMOHAMMADI, Mohsen (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Pirzadeh Z, Ghofrani M, Mollamohammadi M. Plasma Pyridoxal 5´-Phosphate Level in Children with Intractable and Controlled Epilepsy. Iran J Child Neurol. Spring 2017; 11(2):31-36. Abstract Objective Intractable epilepsy is a serious neurologic problem with different etiologies. Decreased levels of pyridoxal phosphate in cerebral spinal fluid of patients with intractable epilepsy due to pyridoxine dependency epilepsy are reported. The aim of this study was to compare plasma pyridoxal 5´-phosphate level in patients with intractable and controlled epilepsy. Materials & Methods This cross- sectional analytic study included 66 epileptic children, 33 patients with controlled and 33 patients with intractable epilepsy, after neonatal period up to 15 yr old of age. Thirty-three patients with intractable epilepsy (10- 162 months) and 33 patients with controlled epilepsy (14-173 months) were enrolled. The study was conducted in Pediatric Neurology Clinic of Mofid Children Hospital, Tehran, Iran from January 2010 to December 2010. Patients’ clinical manifestations, laboratory and neuroimaging findings were collected. Non-fasting plasma 5´- pyridoxal phosphate levels of these subjects were assessed by high-pressure liquid chromatography. Results Mean plasma 5´- pyridoxal phosphate level (PLP) in patients with controlled epilepsy was 76.78±37.24 (nmol/l) (15.5-232.4). In patients with intractable epilepsy, mean plasma 5´- pyridoxal phosphate was 98.67± 80.58 (25.5- 393) nmol/l. There was no statistically significant difference between plasma pyridoxal phosphate levels of these two groups (P═0.430). Conclusion Pyridoxine dependent epilepsy is under diagnosed because it is manifested by various types of seizures. Plasma pyridoxal phosphate levels did not differ in our patients with intractable or controlled epilepsy. If PDE is suspected on clinical basis, molecular investigation of ALDH7A1 mutations, as feasible test, until PDE biomarkers becomes available is recommended. References 1.Cown LD. The epidemiology of the epilepsies in children. Ment Retard Dev Disabil Res Rev 2002;8(3):171-81. 2.French JA. Refractory epilepsy: clinical overview. Epilepsia 2007;48 Suppl 1:3-7. 3.Oliveira R, Pereira C, Rodrigues F, Alfaite C, Garcia P, Robalo C, et al. Pyridoxine-dependent epilepsy due to antiquitin deficiency: achieving a favourable outcome. Epileptic Disord 2013;15(4):400-6. 4.Baxter P. Pyridoxine-dependent and pyridoxine-responsive seizures. Dev Med Child Neurol 2001; 43(6):416-20. 5.Akhoondian J, Talebi S. High dose oral pyridoxine for treatment of pediatric recurrent intractable seizure. MJIRI 2004; 17(4):301-4. 6.Ramachandrannair R, Parameswaran M. Prevalence of pyridoxine dependent seizures in south Indian children with early onset intractable epilepsy: A hospital based prospective study. Eur J Paediatr Neurol 2005;9(6):409- 13. 7. Baxter P. Epidemiology of pyridoxine dependent and pyridoxine responsive seizures in UK. Arch Dis Child 1999;81(5):431-3. 8. Yaghini O, Shahkarami MA, Shamsaii S. Neglected atypical pyridoxine dependent seizures. Iran J Pediatr 2010;20(4):498-501. 9. Lumeng L, Lui A, Li TK. Plasma content of B6 vitamers and its relationship to hepatic rat B6 metabolism. J Clin Inves 1980;66(4):686-95. 10. Clayton PT. B6-responsive disorders: a model of vitamin dependency. J Inherit Metab Dis 2006;29(2-3):317-26. 11. Goyal M, Fequiere PR, McGrath TM, Hyland K. Seizures with decreased levels of pyridoxal phosphate in cerebrospinal fluid. Pediatr Neurol 2013;48(3):227-31. 12. Footitt EJ, Heales SJ, Mills PB, Allen GF, Oppenheim M, Clayton PT. Pyridoxal 5’-phosphate in cerebrospinal fluid; factors affecting concentration. J Inherit Metab Dis 2011; 34(2):529-38. 13. Morris MS, Picciano MF, Jacques PF, Selhub J. Plasma pyridoxal 5’-phosphate in the US population: the National Health and Nutrition Examination Survey, 2003-2004. Am J Clin Nutr 2008;87(5):1446-54. 14. Setiawan B, Giraud DW, Driskell JA. Vitamin B-6 inadequacy is prevalent in rural and urban Indonesian children. J Nutr 2000;130(3):553-8. 15. Shin YS, Rasshofer R, Endres W. Pyridoxal-5’-phosphate concentration as marker for vitamin-B6-dependent seizures in the newborn. Lancet 1984;2(8407):870-1. 16. Pérez B, Gutiérrez-Solana LG, Verdú A, Merinero B, Yuste-Checa P, Ruiz-Sala P, et al. Clinical, biochemical, and molecular studies in pyridoxine-dependent epilepsy. Antisense therapy as possible new therapeutic option. Epilepsia 2013;54(2):239-48. 17. Gospe SM. Pyridoxine-dependent seizures: findings from recent studies pose new questions. Pediatr Neurol 2002;26(3):181-5. 18. Plecko B, Hikel C, Korenke GC, Schmitt B, Baumgartner M, Baumeister F, et al. Pipecolic acid as a diagnostic marker of pyridoxine-dependent epilepsy. Neuropediatrics 2005;36(3):200-5. 19. Albersen M, Groenendaal F, van der Ham M, de Koning TJ, Bosma M, Visser WF, et al. Vitamin B6 vitamer concentrations in cerebrospinal fluid differ between preterm and term newborn infants. Pediatrics 2012;130(1):e191-8. 20. Ormazabal A, Oppenheim M, Serrano M, García-Cazorla A, Campistol J, Ribes A, et al. Pyridoxal 5’-phosphate values in cerebrospinal fluid: reference values and diagnosis of PNPO deficiency in paediatric patients. Mol Genet Metab 2008;94(2):173-7. 21. Stockler S, Plecko B, Gospe SM Jr, Coulter-Mackie M, Connolly M, van Karnebeek C, Mercimek-Mahmutoglu S, Hartmann H, Scharer G, Struijs E, Tein I, Jakobs C, Clayton P, Van Hove JL. Pyridoxine dependent epilepsy and antiquitin deficiency: clinical and molecular characteristics and recommendations for diagnosis, treatment and follow-up.Mol Genet Metab. 2011 Sep- Oct;104(1-2):48-60. doi: 10.1016/j.ymgme.2011.05.014. Epub 2011 May 24. 22. Steinberg SJ, Dodt G, Raymond GV, Braverman NE, Moser AB, Moser HW. Peroxisome biogenesis disorders. Biochim Biophys Acta 2006;1763(12):1733-48. 23. Mills PB, Struys E, Jakobs C, Plecko B, Baxter P, Baumgartner M, et al. Mutations in antiquitin in individuals with pyridoxine-dependent seizures. Nat Med 2006;12(3):307-9. 24. Struys EA, Nota B, Bakkali A, Al Shahwan S, Salomons GS, Tabarki B. Pyridoxine-dependent epilepsy with elevated urinary α-amino adipic semialdehyde in molybdenum cofactor deficiency. Pediatrics 2012; 130(6):e1716-9. 25. Struys EA, Bok LA, Emal D, Houterman S, Willemsen MA, Jakobs C. The measurement of urinary Δ¹- piperideine-6-carboxylate, the alter ego of α-aminoadipic semialdehyde, in Antiquitin deficiency. J Inherit Metab Dis 2012;35(5):909-16. 26. Nam SH, Kwon MJ, Lee J, Lee CG, Yu HJ, Ki CS, et al. Clinical and genetic analysis of three Korean children with pyridoxine-dependent epilepsy. Ann Clin Lab Sci 2012;42(1):65-72. 27. Yang Z, Yang X, Wu Y, Wang J, Zhang Y, Xiong H, et al. Clinical diagnosis, treatment, and ALDH7A1 mutations in pyridoxine-dependent epilepsy in three Chinese infants. PLoS One 2014;9(3):e92803. 28. Jung S, Tran NT, Gospe SM Jr, Hahn SH. Preliminary investigation of the use of newborn dried blood spots for screening pyridoxine-dependent epilepsy by LC-MS/MS. Mol Genet Metab 2013;110(3):237-40.